The Effect of Facilities and Service Quality on Inpatient Satisfaction at Ngimbang Hospital, Lamongan Regency - Siti Kholifah; M.Yaskun; Nurul Badriyah (Sean Institute, 2024)
This study aims to analyze the influence of facilities, quality, and price on consumer satisfaction at Welijo Cafe and Freshmarket. The study used a quantitative approach with the consumer population of Welijo Cafe and Freshmarket over the past three months as many as 3,093 consumers. The sample was determined using the Slovin formula with an error rate of 10%, so that 97 respondents were obtained. The sampling technique uses simple random sampling. Primary data were collected through a Likert scale questionnaire and analyzed using SPSS version 25 through validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and coefficient of determination. The results of the study showed that facilities had a positive and significant effect on consumer satisfaction with a t-value of 3.054 and a significance of 0.003. Quality had a positive and significant effect with a t-value of 3.846 and a significance of 0.000. Price also has a positive and significant effect with a t-value of 2.603 and a significance of 0.011. Simultaneously, facilities, quality, and price had a significant effect on consumer satisfaction with an F value of 68.342 and a significance of 0.000. The R Square value of 0.688 indicates that the three independent variables explain 68.8% of the variation in consumer satisfaction. Quality variables are the most dominant factor in influencing consumer satisfaction.